AN AGENT-BASED-MODELING FOR ELECTORAL PREFERENCE BEHAVIOR: PRESIDENTIAL ELECTIONS OF THE DOMINICAN REPUBLIC 2012 - Pedro Taveras N. (European Scientific Journal, ESJ, 2013)
An agent based model was constructed under the assumption that political preferences of individuals change over the campaign because of social interaction and the influence of global information. During the voting decision process take place a phenomenon known as social contagion, aside from institutional factors and personal preferences. Therefore, voters’ change of mind may arise and voter’s decision analysis might be influenced by polls or commercial campaign.